The Effect of 1% Povidone Iodine Mouthwash on The Incidence of Oral Mucositis and Odynophagia in Patients with Head and Neck Malignancy - Handayani, Peny; Budiarti, Rery; Yusmawan, Willy; Antono, Dwi; Dewi, Anna Mailasari Kusuma; Widodo , Pujo (RSUP Dr. Kariadi, 2023)
BACKGROUND: Oral mucositis is an injury of normal mucosal tissue with an acute inflammation of the oral, tongue, and pharyngeal mucosa after exposure to chemo-radiotherapy. Post chemoradiotherapy oral mucositis is commonly accompanied by painful swallowing or odynophagia. Povidone iodine 1% is an antiseptic mouthwash that widely used to prevent infections in the oral cavity. OBJECTIVE: The aim of this study was to determine the effect of 1% povidone iodine mouthwash on the incidence of oral mucositis in patients with head and neck malignancy at Dr. Kariadi General Hospital Semarang. METHOD: This study was single random blinded experimental study, with total samples of 44 patients with head and neck malignancy after chemoradiotherapy. The samples divided into treatment group of 22 samples with 1% povidone iodine mouthwash and control group of 22 samples with NaCl 0.9% recruited using single random sampling at Dr. Kariadi Semarang General Central Hospital in 2022. The effect of 1% povidone iodine mouthwash on the incidence of oral mucositis and odynophagia was analyzed using the Fischer Exact and Mann Whitney test. RESULT: In the 1% povidone iodine mouthwash group day 15th, 21 patients (95.5%) were found without mucositis and 1 patient (4.5%) with mucositis oral grade I. In the 1% povidone iodine mouthwash group, 21 people (4.5%) were found without odynophagia and 1 people (4.5%) had odynophagia. There was an association between oral mucositis and odynophagia on povidone iodine 1% group (p < 0.05). CONCLUSION: Povidone iodine 1% mouthwash can affect the incidence of oral mucositis in patients with head and neck carcinoma. Povidone iodine 1% mouthwash can reduce the incidence of oral mucositis and odynophagia compared to placebo in patients with head and neck carcinoma.